Comparison of intravitreal anti-vascular endothelial growth factor agents and treatment results in Irvine-Gass syndrome - Fahrettin Akay; Mehmed Uğur Işık; Berkay Akmaz; Yusuf Ziya Güven (Press of International Journal of Ophthalmology (IJO Press), 2020)
To compare the efficacy of bevacizumab, ranibizumab, and aflibercept in pseudophakic cystoid macular edema (CME) patients with Irvine-Gass syndrome (IGS).This study is designed as retrospective consecutive case series. Those who developed postoperative pseudophakic CME that refractory to topical treatment and were treated with anti-vascular endothelial growth factor (VEGF) agents included in the study. Optical coherence tomography (OCT) examination including central macular thickness (CMT), total macular volume (TMV), retinal nerve fiber layer (RNFL), ganglion cell layer (GCL) and choroidal thickness (ChT) measurements at the baseline, 1st, 3rd and 6th month controls were performed.Fifty-nine eyes of 59 patients with CME and other healthy eyes of the patients (Control group) were evaluated. There were 22 eyes of 22 patients in the bevacizumab group (group 1), 19 eyes of 19 patients in the ranibizumab group (group 2), and 18 eyes of 18 patients in the aflibercept group (group 3). There was no difference in terms of age, gender, axial length, IOP, and spherical equivalent values. The baseline subfoveal and mean ChT were higher in the IGS group. The difference between the baseline and sixth month values of subfoveal and mean ChT were compared in the CME groups, thinning was observed in all three groups. GCL was thinner in the patient group at the 6th month of treatment. The resolution time of CME was observed faster in group 1.All three anti-VEGF agents seem to be effective in CME but bevacizumab appears to be slightly more cost-effective than the other two alternatives.
Keywords: choroidal thickness; Ophthalmology; macular edema; irvine-gass syndrome; ganglion cell complex; anti-vegf agents; RE1-994; 3. Good health